The role of human-induced pluripotent stem cells in studying cardiac channelopathies - Begovic, Merima; Schneider, Luca; Zhou, Xiao-Bo; Hamdani, Nazha; Akın, Ibrahim; El-Battrawy, Ibrahim (International journal of molecular sciences, 2024)
Cardiac channelopathies are inherited diseases that increase the risk of sudden cardiac death. While different genes have been associated with inherited channelopathies, there are still subtypes, e.g., catecholaminergic polymorphic ventricular tachycardia and Brugada syndrome, where the genetic cause remains unknown. Various models, including animal models, heterologous expression systems, and the human-induced pluripotent stem-cell-derived cardiomyocytes (hiPSCs-CMs) model, have been used to study the pathophysiological mechanisms of channelopathies. Recently, researchers have focused on using hiPSCs-CMs to understand the genotype-phenotype correlation and screen drugs. By combining innovative techniques such as Clustered Regularly Interspaced Short Palindromic Repeats/Clustered Regularly Interspaced Short Palindromic Repeats associated protein 9 (CRISPR/Cas9)-mediated genome editing, and three-dimensional (3D) engineered heart tissues, we can gain new insights into the pathophysiological mechanisms of channelopathies. This approach holds promise for improving personalized drug treatment. This review highlights the role of hiPSCs-CMs in understanding the pathomechanism of Brugada syndrome and catecholaminergic polymorphic ventricular tachycardia and how these models can be utilized for drug screening.
Gesehen am 30.04.2025